HUBUNGAN KADAR VITAMIN D SERUM DENGAN KUALITAS HIDUP PADA PASIEN EPILEPSI - Edith Fitriyana Girsang,* Aris Catur Bintoro,* Dwi Pudjonarko* (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION EPILEPSY AFFECTS OVERALL HEALTH STATUS AND DECREASES THE LIFE QUALITY OF EPILEPSY PATIENT SEIZURE FREQUENCY SEIZURE TYPE DAILY ACTIVITY DISORDER DEPRESSION AND ANXIETY ALSO AFFECT THE QUALITY OF LIFE EPILEPSY PATIENT VITAMIN D IS CONSIDERED AS A NEUROSTEROID MODULATOR OF NERVE EXCITABILITY AND SEIZURE SUSCEPTIBILITY STUDIES OF VITAMIN D DIRECT ROLE IN EPILEPSY ARE LIMITED NEVERTHELESS SOME STUDIES SHOW THE ROLE OF VITAMIN D AS AN ANTICONVULSANT THAT REDUCES THE INCIDENCE OF SEIZURES